Commitments and Disclosure in Oligopolies - Hughes, John S.; Williams, Michael G. (The Accounting Review, 2008)
In this paper, we examine the welfare effects of pre-production commitments made by firms competing in oligopoly markets and disclosure of such commitments. By commitments we refer to any device that provides a strategic incentive to alter production choices. Examples include forward contracts, capital structure, research and development investment, terms of compensation, and cost allocation. If the only purpose underlying commitment is to gain a strategic advantage in product market competition, then the result with disclosure can be characterized by Stackelberg warfare. Many potential commitments have non-strategic effects, implying a trade-off when optimizing, with imperfect achievement of both strategic (deterring rival production) and non-strategic goals. However, given disclosure, we show that in the limit as the number of commitment devices becomes large, firms achieve full Stackelberg warfare and total realization of non-strategic goals. Disclosure in this context is social welfare enhancing.